Perbedaan Kadar Gula Darah Puasa Setelah Melakukan Senam Zumba pada Wanita yang Mengalami Obesitas di Pusat Kebugaran Bandar Lampung - Agustina, Mezza; Khairunnisa; Oktarlina, Rasmi Zakiah (Medula, 2024)
Obesity is a global epidemic health problem and the cases continue to increase every year. Obesity is a predisposing factor for an increase in blood sugar levels. A relatively simple and easy way to prevent obesity and control blood sugar levels is to exercise regularly. One of them is the zumba exercise. During exercise, muscle cells use more glucose and other nutrient fuels than usual for muscle contraction activities. During physical activity, insulin sensitivity increases and causes a decrease in plasma blood sugar levels. This study aims to determine differences in fasting blood sugar levels for those who have exercised for the first time and who have done exercise twelve times in obese women. This research is an observational analytic study with a cross-sectional approach. In this study, fasting blood sugar levels were measured in 52 respondents who took part in zumba exercises at Fitness Center Bandar Lampung. Sampling was carried out on respondents who did zumba exercise for the first time and who had done zumba exercise twelve times. The results showed that the average fasting blood sugar levels for those who had exercised for the first time and who had done exercise twelve times were 98.65 and 91.38 mg/dl, respectively. Based on statistical tests, zumba exercise has a significant difference in changes in the value of fasting blood sugar levels in obese women who have done exercise.